PENGARUH PENGGUNAAN GADGET TERHADAP MINAT BELAJAR SISWA KELAS V DI SD INPRES TAMALANREA II MAKASSAR - Ince Prabu Setiawan Bakar (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: The effect of using gadgets on the learning interest of fifth grade students at SD Inpres Tamalanrea II Makassar. This study aims to determine the effect of using gadgets on the learning interest of fifth grade students at SD Inpres Tamalanrea II Makassar. This type of research is a correlational study which is used to determine the relationship and the level of the relationship between the two. The population of this study were all students of grade V SD Tamalanrea, amounting to 73 people. While the research sample is 26 people. Data collection was carried out by distributing questionnaires and documentation. The data collected in the study were analyzed using descriptive and inferential statistical techniques. Based on the results of data analysis, it can be seen that the results of the questionnaire on the use of gadgets are 1759 and the results of the questionnaire for learning interest are 1777.The descriptive data analysis of the use of gadgets is an average of 67.65, median 67.50 mode 63 and a standard deviation of 4.137, while the data analysis of interest in learning is average. - mean 68.35, median 68.50 mode 73 and standard deviation 5.396. Inferential data analysis, namely normality test normally distributed because the p-value> 0.05 and the homogeneity test, is said to be homogeneous because it is 0.061> 0.05. The correlation hypothesis test with 26 students has a correlation of 0.889 from the t table 0.388. Thus, t count> t table, at the level of the correlation coefficient between 0.70-0.90, including the high level. This shows that the value of data analysis is higher than the value of r table, so the proposed research hypothesis is accepted.Keywords: Gadgets and Interest in Learning